The role of nurses in the prevention and management of obesity - Lazarou, Chrystalleni; Kouta, Christiana (My University, 2010)
This paper examines the current scientific knowledge on the relationship between diet and obesity, and considers the implications for nursing practice. It focuses on the main nutritional elements that have been identified as significant in the prevention and management of obesity. Research findings reveal the important role of specific dietary habits and patterns and their influence on obesity; particularly on childhood obesity. This paper discusses the nursing implications in relation to the prevention and management of obesity.
Keywords: Obesity; Cardiovascular disease; Management; Health promotion; Diet; Prevention; Nutrition; Micronutrients; Nursing applications